2015
DOI: 10.18052/www.scipress.com/ilshs.51.106
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Corporate Governance on Firm Financial Performance in Islamic Financial Institution

Abstract: The paper discusses the influence and relationship between corporate governance practices and firm financial performance in Islamic banking sector. Main purpose of this study is to find or identify various factors or variables that affects the firm financial performance. Corporate governance focuses on three meters as board size, number of meeting and audit committee size and firm financial performance has also three indicators return on equity, return on asset and earning per share. Data relates to corporate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 3 publications
4
22
0
Order By: Relevance
“…Furthermore, the more often the BOD organizes meetings, the risk of credit will be more intensively monitored and thus the NPF is expected to be controlled. Iqbal, Haider, & Khan (2015) find that the number of meeting boards has a positive significant effect on the financial performance (Return on Assets/ROA) of Islamic banks in Pakistan. Gafoor, Mariappan, & Thyagarajan (2018) also find a similar result between board meetings and bank performance (ROA) in India.…”
Section: Board Of Directors and Credit Risk: An Empirical Study Of Inmentioning
confidence: 83%
See 1 more Smart Citation
“…Furthermore, the more often the BOD organizes meetings, the risk of credit will be more intensively monitored and thus the NPF is expected to be controlled. Iqbal, Haider, & Khan (2015) find that the number of meeting boards has a positive significant effect on the financial performance (Return on Assets/ROA) of Islamic banks in Pakistan. Gafoor, Mariappan, & Thyagarajan (2018) also find a similar result between board meetings and bank performance (ROA) in India.…”
Section: Board Of Directors and Credit Risk: An Empirical Study Of Inmentioning
confidence: 83%
“…According to Ginena (2014), good governance will enhance the supervision system that is efficient and cost-effective for capital allocation by the manager. Iqbal, Haider, & Khan (2015) state that corporate governance has a positive relationship with the financial performance of Islamic banks in Pakistan. Furthermore, the success of the implementation of corporate governance in Islamic banks needs supporting facilities such as internal control, risk management, and prudent regulation and supervision (Budiman, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Further, the financial sector of Pakistan as a whole has been ignored by the researchers with regard to the impact of corporate governance practices and earnings management (Rehman & Mangla, 2010). Haider, Khan, and Iqbal (2015) conducted a similar study to check the relationship between corporate governance practices and financial performance in the Islamic banking segment in Pakistan and found a positive connection in this regard. Burki and Ahmad (2007) conducted a similar study to review the effect of changes in the governance on the performance of banks in Pakistan and discovered that financial distress affects the performance of banks.…”
Section: Introductionmentioning
confidence: 99%
“…Some previous studies concluded that firm performance in modern business perspective is influenced by board size, Board independence, and enterprise risk management (ERM). Meanwhile, resource dependence theory that the larger board size will be followed by better firm performance (Anum Mohd Ghazali, 2010) , Moreover, some studies found that the large board size will increase the effectiveness of corporate oversight, which will have an impact on improving firm performance (Pearce and Zahra, 1992; Kumar Adhikary, Huynh Gia Hoang Bishnu Kumar Adhikary and Huynh Gia Hoang, 2014; Haider, Khan and Iqbal, 2015). In contrast, (Hermalin and Weisbach, 2001)conclude that small board size tends to improve firm performance (JENSEN, 1993;Yermack, 1996;Nisha and Ghosh, 2018).…”
Section: Introductionmentioning
confidence: 99%